Development of Interactive Learning Media In Basic Programming Subjects Based on Learning Management System (LMS) - Nurhayat Candra Kusumah (Publikasi Indonesia, 2023)
Interactive Learning Media has a very important role in the process of teaching and learning activities (KBM) in schools, especially during a pandemic, where KBM activities must be carried out online (in a network). To streamline online learning activities are stored in the Learning Management System (LMS), which is a web-based software program for management, documentation, monitoring, reporting, administration and distribution of educational content, training programs, technical manuals, instructional videos or digital library materials, and projects learning and development. Interactive Learning Media is a multimedia-based tool that can describe messages or information from teacher to students in which active two-way communication occurs between multimedia and users (students) so that it can facilitate the online learning process. This study used the Multimedia Development Life Cycle (MDLC) method with six stages, namely: concept, design, material collecting, assembly, testing, and distribution. The research objective is to create interactive learning media for basic programming subjects using Articulate Storyline software. The results of designing learning media are in the form of a scom application that can be integrated into the school's Learning Management System (LMS) and can be accessed by students anywhere and anytime via a laptop or smartphone.